Implementation and Evaluation of Competency-based Medical Education in Phase I of Undergraduate Medical Curriculum - KRISHNAMURTHY SOUNDARIYA; GANAPATHY KALAISELVAN; MAHENDRAN RAJALAKSHMI; RAGHAVAN SINDHURI (Journal of Advances in Medical Education and Professionalism, 2022)
Introduction: Adaptation to the “Competency-based Medical Education” (CBME) is a major challenge faced by medicalcolleges all over India. Hence, the present study aimed to evaluate the mechanisms adopted in the process of implementation of CBME in Phase I at our institution.Methods: In this qualitative study, 12 faculty members including professors, associate professors, assistant professors, and tutors from preclinical departments of the first professional year participated as the study participants. Focus Group Discussion were conducted with the participants regarding the strategies adopted and the challenges faced in implementation of CBME. Gap analysis was done based on the guidelines from CBME modules. In depth interview was conducted with the heads of the pre-clinical departments to propose appropriate action plans. The interviews were audio-recorded and thematic analysis of the transcripts was done.Results: The crucial areas identified were the implementation of early clinical exposure, AETCOM, integrated, and skill modules during the COVID pandemic. The faculty expressed lack of clarity in designing the sessions for “Self-Directed Learning”. Tapering the content relevant to basic sciences was a major challenge faced in the integrated sessions. The faculty members requested sensitization to different student centric instructional methods for small group teaching and guidelines for valid assessment strategies.Conclusions: Acquisition of competencies is enhanced by appropriate instructional methods and effective assessmentstrategies. Frequent and constant hands-on training on the CBME modules through “Faculty Development Programs” plays a crucial role in the successful implementation of CBME.